2015
DOI: 10.1111/1750-3841.13137
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SNF1 on Maltose Metabolism and Leavening Ability of Baker's Yeast in Lean Dough

Abstract: Maltose metabolism of baker's yeast (Saccharomyces cerevisiae) in lean dough is negatively influenced by glucose repression, thereby delaying the dough fermentation. To improve maltose metabolism and leavening ability, it is necessary to alleviate glucose repression. The Snf1 protein kinase is well known to be essential for the response to glucose repression and required for transcription of glucose-repressed genes including the maltose-utilization genes (MAL). In this study, the SNF1 overexpression and deleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…The effective glucose and MAL62 derepression by TUP1 overexpression could facilitate the rapid transition from glucose to maltose metabolism and the efficient maltose hydrolysis, resulting in improved maltose metabolism and dough leavening ability upon TUP1 overexpression. This finding corresponded with that of Zhang et al [ 28 ], who reported that the enhancing MAL expression levels by glucose derepression in SNF1 (encoding for the catalytic subunit of Snf1 protein kinase, playing a significant role in relieving glucose repression by inactivating the transcription repressor Mig1) overexpression improved the ability of baker’s yeast strain to utilize maltose and leaven lean dough. In addition, overexpression of TUP1 could enhance the specific growth rate and biomass yield of baker’s yeast.…”
Section: Discussionsupporting
confidence: 90%
“…The effective glucose and MAL62 derepression by TUP1 overexpression could facilitate the rapid transition from glucose to maltose metabolism and the efficient maltose hydrolysis, resulting in improved maltose metabolism and dough leavening ability upon TUP1 overexpression. This finding corresponded with that of Zhang et al [ 28 ], who reported that the enhancing MAL expression levels by glucose derepression in SNF1 (encoding for the catalytic subunit of Snf1 protein kinase, playing a significant role in relieving glucose repression by inactivating the transcription repressor Mig1) overexpression improved the ability of baker’s yeast strain to utilize maltose and leaven lean dough. In addition, overexpression of TUP1 could enhance the specific growth rate and biomass yield of baker’s yeast.…”
Section: Discussionsupporting
confidence: 90%
“… 2014 , 2015b ; Zhang et al . 2015a , b ). Alternatively, maltose utilization can be improved by selecting mutants on medium containing fermentable maltose with non-metabolizable glucose analogs.…”
Section: Primary Fermentation Metabolites: Co 2 mentioning
confidence: 99%
“…The surviving cells maintained strong growth and metabolism abilities of baker' yeast, which ensured strong fermentation ability after freezing. Overexpression of SNF1 could effectively enhance the maltose utilization and dough leavening ability of industrial baker's yeast [38], which is also reflected after freezing stress. Snf1 regulated glycerol metabolism via the regulation of the transcription factor Adr1 in glucose [39].…”
Section: Glycerophospholipid Metabolism Cho2 Psd2 Spo14 Ale1 Gpd2mentioning
confidence: 99%
“…The plasmids Yep-PSK and Yep-PK were transferred to the parental strain ABY3 using lithium acetate/PEG procedure according to the previous study [38]. The transformants ABY+S and ABY+YP were verified by PCR using the primers PGK-F/PGK-R and K-F/K-R shown in Table 4.…”
Section: Transformation Of Yeastmentioning
confidence: 99%